One-year Results of Aflibercept Treatment for Polypoidal Choroidal Vasculopathy with Good Visual Acuity - Kwon, Ji Min; Pak, Kang Yeun; Lee, Jae Jung; Sagong, Min; Kim, Hyun Woong (Korean journal of ophthalmology, 2021)
To evaluate the one-year efficacy of intravitreal aflibercept injection in polypoidal choroidal vasculopathy (PCV) with best-corrected visual acuity (BCVA) of 20 / 40 or better. This was a multicenter retrospective study. The medical records of patients diagnosed with treatment-naïve PCV were retrospectively reviewed. Patients with an initial BCVA of 20 / 40 or better and who had undergone intravitreal aflibercept injection were included. Patients were treated with three consecutive monthly injections, followed by pro re nata regimen according to the clinician's discretion at variable interval visits. The proportions of eyes for which BCVA was maintained (≤ 0.2 logarithm of the minimum angle of resolution change) or improved at 12 months were evaluated. The changes of BCVA, central subfield macular thickness (CSMT), pigment epithelial detachment, and subretinal fluid also were assessed. A total of 86 eyes were included. The mean number of injections for 12 months of treatment was 5.4 ± 1.7. BCVA was maintained or improved in 94.2% (81 / 86) of cases. Mean BCVA (logarithm of the minimum angle of resolution) had changed from the baseline (0.23 ± 0.09) at 3 months (0.21 ± 0.14), 6 months (0.24 ± 0.22), and 12 months (0.20 ± 0.18), but with no statistical significance. CSMT had improved significantly from the baseline (336.1 ± 97.3 μm) at 3 months (223.6 ± 47.22 μm), 6 months (239.6 ± 64.2 μm), and 12 months (223.8 ± 47.9 μm). Pigment epithelial detachment was observed in 93% of cases at the baseline, 72.1% at 3 months, and 69.8% at 12 months, showing a significant decrease at all observation points. Subretinal fluid was observed in 91.9% of cases at the baseline, 20.9% at 3 months, and 29.1% at 12 months, showing a significant decrease at all observation points. In cases of PCV with good visual acuity, intravitreal aflibercept injections decreased CSMT and were effective in maintaining visual acuity.